Central neurotoxicity induced by trastuzumab emtansine (T-DM1): a case report. Issue 10 (November 2021) - Papageorgiou, Georgios I.; Symeonidis, David G.; Tsakatikas, Sergios A.; Liatsos, Alexandros D.; Douglas, Konstantinos A. A.; Douglas, Vivian P.; Moschos, Marilita M.; Kosmas, Christos
Abstract : Trastuzumab emtansine (T-DM1) is a human epidermal growth factor receptor 2 (Her2) – targeted antibody-drug conjugate that is approved for patients previously treated with trastuzumab and a taxane for Her2-positive advanced breast cancer and those who have progressed within 6 months of completion of adjuvant chemotherapy, as well as for patients with residual invasive Her2-positive disease after the completion of adjuvant chemotherapy. Peripheral neuropathy is a common adverse event; however, ocular events have also been described. With the current report we present the case of a 67-year old woman who developed transient grade 2–3 blurred vision after the first T-DM1 infusion, which was complicated with grade 2 diplopia causing vertigo after the second infusion. After extended investigation, this symptomatology was attributed to central neurotoxicity, and gradually resolved after T-DM1 discontinuation.